2018
DOI: 10.1016/j.vaccine.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

A Phase III open-label, randomized, active controlled clinical study to assess safety, immunogenicity and lot-to-lot consistency of a bovine-human reassortant pentavalent rotavirus vaccine in Indian infants

Abstract: HighlightsPentavalent reassortant rotavirus vaccine (BRV-PV) was tested for lot-to-lot consistency in Indian infants.The vaccine demonstrated safety profile similar to licensed Rotarix®.Lot-to-lot consistency in the immunogenicity of BRV-PV was demonstrated in terms of GMC ratios of IgA antibodies.The immune responses between the pooled BRV-PV arms and Rotarix® were comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…None of the SAEs was causally related to the vaccine, in both the groups. There were no safety concerns associated with co-administration of oral Rotavirus vaccine, consistent with studies done for concomitant administration of DT based hexavalent 16 and pentavalent 19 vaccines with oral rotavirus vaccines.…”
Section: Discussionsupporting
confidence: 78%
“…None of the SAEs was causally related to the vaccine, in both the groups. There were no safety concerns associated with co-administration of oral Rotavirus vaccine, consistent with studies done for concomitant administration of DT based hexavalent 16 and pentavalent 19 vaccines with oral rotavirus vaccines.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, a Phase III clinical study was reported for the safety, immunogenicity, and lot-to-lot consistency of 3Ds of RotaSIIL ® with 2Ds of Rotarix ® and a dose of placebo in 6–8-weeks-old Indian infants, who had earlier received HepB and OPV vaccines at birth. The IgA GMC ratios among the lots A, B, and C considered ranged from 0.99 to 1.07 [ 293 ]. In terms of IgA seropositivity to RoVs, there was a 46.98% rate with RotaSIIL ® vs. 31.12% with Rotarix ® [ 293 ].…”
Section: Factors Affecting Rotavirus Vaccine Efficiencymentioning
confidence: 99%
“…The IgA GMC ratios among the lots A, B, and C considered ranged from 0.99 to 1.07 [ 293 ]. In terms of IgA seropositivity to RoVs, there was a 46.98% rate with RotaSIIL ® vs. 31.12% with Rotarix ® [ 293 ]. All forms of reactogenic effects remained the same across the lots and RotaSIIL ® vs. Rotarix ® combined vaccines.…”
Section: Factors Affecting Rotavirus Vaccine Efficiencymentioning
confidence: 99%
“…Safety data generated in this study further support previous evidence that 2 doses of Lyo HRV are well tolerated in infants worldwide, 12,22,24 including in India. 18,25,26 In this study, no intussusception cases were reported following administration of HRV, but one infant who received Liq HRV experienced intestinal obstruction, which was resolved within 4 days from onset. No safety concern was observed for either Liq or Lyo HRV administration during the current study, in line with the favorable benefit/risk profile established for RV vaccines.…”
Section: Discussionmentioning
confidence: 64%